Collaborative lifelong learning and professional transfer. Case study: ECO European Project. Issue 1 (2nd January 2019) - Marta-Lazo, Carmen; Frau-Meigs, Divina; Osuna-Acedo, Sara
ABSTRACT: This research reviews the formative model of the sMOOCs (social MOOC) characterized by the interaction and the implication of the participants who, relying on collective intelligence, look for the co-creation of knowledge in every educational action. The fieldwork focuses on the analysis of the "Step by Step" sMOOC of ECO Project (the second and third editions), that aims at the training of e-teachers and the transfer of learning to the professional field. The research methodology is mixed, with quantitative and qualitative techniques: it uses a semi-structured questionnaire, in order to compare possible bivariate correlations between the different variables; it conducts a content analysis of the fragments of messages written by the participants in the forums of the course. One of the most significant conclusions is the high degree of satisfaction of the participants with regard to the value of the course for their professional life. This form of transfer of the learning process leads to the proposal of a new modality for MOOCs, the tMOOC as "transferMOOC".